Low Serum Calcium Concentration in Patients With Systemic Lupus Erythematosus Accompanied by the Enhanced Peripheral Cellular Immunity - Du, Xue; Zhao, Di; Wang, Ying; Sun, Zhengyi; Yu, Qiuyang; Jiang, Hongyu; Wang, Liying (Frontiers in Immunology, 2022)
Objective: This study aims to explore the relationship between serum calcium concentration and peripheral lymphocyte status / Th1/Th2 cytokine levels in SLE patients, and the effect of glucocorticoids (GCs) on the calcium concentration and immune cell activation. Methods: The peripheral blood TBNK lymphocyte subsets and Th1/Th2 cytokines in SLE patients with low or normal serum calcium concentration and healthy people were analyzed and compared retrospectively. Peripheral white blood cells (PWBCs) from SLE patients or healthy people were stimulated with PMA or GCs in vitro to test their extracellular calcium concentration and CD8+ T cell activation. Results: The percentages of CD8+ T and NK cells in SLE patients increased, but the increase of the number of CD8+ T cells only occurred in the SLE patients with low serum calcium concentration, and the number of CD45hiCD8+ T cells also increased, suggesting that SLE patients with hypocalcemia tend to possess an enhanced cellular immunity. The results of Th1/Th2 cytokines in peripheral blood showed that the levels of serum IL-2, IL-10, IL-6 and IFN-γ in SLE patients with hypocalcemia were significantly increased. Although the serum levels of TNF-α in SLE patients were similar to that in healthy people, it was significantly higher than that in SLE patients with normal serum calcium. When comparing the results of Th1/Th2 cytokines in two times of one patient, the serum levels of TNF-α in SLE patients increased while serum calcium levels decreased. The in vitro experiments showed that the decrease of serum calcium concentration in SLE patients was affected by the immune cell activation and the application of GCs, but GCs did not promote the immune cell activation. Conclusions: Low serum calcium may make SLE patients in an enhanced cellular immune status and GCs aggravates the decrease of serum calcium levels but has no role on the immune cell activation. It suggests that hypocalcemia possibly promotes the disease activity of SLE patient, which should be paid attention to clinically.